2022
DOI: 10.3390/biom12030424
|View full text |Cite
|
Sign up to set email alerts
|

ENT-A010, a Novel Steroid Derivative, Displays Neuroprotective Functions and Modulates Microglial Responses

Abstract: Tackling neurodegeneration and neuroinflammation is particularly challenging due to the complexity of central nervous system (CNS) disorders, as well as the limited drug accessibility to the brain. The activation of tropomyosin-related kinase A (TRKA) receptor signaling by the nerve growth factor (NGF) or the neurosteroid dehydroepiandrosterone (DHEA) may combat neurodegeneration and regulate microglial function. In the present study, we synthesized a C-17-spiro-cyclopropyl DHEA derivative (ENT-A010), which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 88 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Considering a wider perspective, our study suggests that MNTs can contribute to combinatorial treatments for CNS injuries by simultaneously enhancing cell therapies and modulating the loss of neuronal tissue. MNT contribution in such treatments could be further enhanced by optimizing MNT dosing, exploiting novel MNT designs that target specific neurotrophin receptors [ 67 , 68 ] or utilizing targeted methods to control their spatiotemporal delivery within CNS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a wider perspective, our study suggests that MNTs can contribute to combinatorial treatments for CNS injuries by simultaneously enhancing cell therapies and modulating the loss of neuronal tissue. MNT contribution in such treatments could be further enhanced by optimizing MNT dosing, exploiting novel MNT designs that target specific neurotrophin receptors [ 67 , 68 ] or utilizing targeted methods to control their spatiotemporal delivery within CNS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous results (Yilmaz et al, 2022 ) that we identified compound ENT-A010 bearing a cyclopropyl group conjugated to an α,β-unsaturated ester as a dual agonist of TrkA and TrkB receptors, we set out to prepare a small series of cyclobutyl derivatives to clarify the optimum size of the C17-spirocyclic moiety. Thus, the C17-cyclobutanone analog ( ENT-A076 ), the α,β-unsaturated cyano ( ENT-A077 ), α,β-unsaturated ethyl ester ( ENT-A079 ), α,β-unsaturated methyl ester ( ENT-A087 ), and α,β-unsaturated acid ( ENT-A080 ) derivatives were prepared.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation conditions were optimized to ensure linear metabolite formation with respect to protein concentration and reaction time. All test compounds were assessed at 1 μM based on our ADMET standard operating procedures and protocols, also published previously (1 μM was selected based on our ADMET standard operating procedures and protocols also published previously) (Rogdakis et al, 2022 ; Yilmaz et al, 2022 ). Approximately 1 mM of NADPH served as a cofactor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations